PERFORMANCE PERTUMBUHAN BEBERAPA POPULASI PATIN SIAM (Pangasianodon hypophthalmus) DI INDONESIA - Solaiman Solaiman; Muhammad Sugihartono (Jurnal Ilmiah Universitas Batanghari Jambi, 2012)
Siamese catfish (Pangasianodon hypophthalmus) is one of the leading freshwater fish introductions from Thailand's rapid development of aquaculture in Indonesia. Improved catfish aquaculture Siamese is characterized by the increasing number of areas such as aquaculture ponds and cages, and the demand for seed production. Based on the reports of farmers and monitoring BBAT Jambi on pangasius farming areas in Jambi are decreasing trend Siamese catfish seed quality, ie seeds with slow growth leading to low quality of seeds produced. To reduce this required moms potential of regional development in Indonesia Siamese catfish that will be used as the basis to produce the parent stem excel. Therefore necessary to test the performance of siamese catfish growth of some populations in Indonesia as a first step to get potential moms in Indonesia. Research conducted at the Institute of Freshwater Aquaculture Jambi during January-March 2011. Test performance against population growth Siamese catfish seed from 7 regions in Indonesia, Jambi, Riau, Lampung, Subang, Bogor, Bekasi and South Kalimantan. Hapa enlargement minimum size 3x2x1, 5 m3 rearing ponds installed in the size of 600 m2 with a water depth of 2 meters. Experimental design is CRD (completely randomized design) with the treatment of fish populations and three replications. Parameters observed were specific daily growth (SGR), survival (survival rate), feed conversion ratio (FCR), water quality, and the level of abnormality. The results showed that the test can peformance growth best in four populations: a population of Lampung, Subang, Riau and South Kalimantan.Keywords: Pangasianodon hypophthalmus, growth, survival, feed conversion